Respons penawaran pengeluar minyak sawit Malaysia : model harta jangkaan - Mohamed Berawi, Fuad (Universiti Utara Malaysia, 2004)
The objective of this study is to determine how Malaysia's palm oil producers form their own price expectation at the time when palm oil supply is made. Five own price expectations were formed according to the process suggested by cobweb theorem, extrapolative, simple weighted,adaptive, and rational expectation hypotheses. Consequently, price expectation was nested in the desired supply model with consideration of partial adjustment hypothesis framework to be tested in the palm oil supply function to illustrate the long term relationship. Research finding has shown that rational expectation hypothesis is best to explain the expectation process in achieving desired supply and shows short run elasticity is lower in relation to long run in all variables. Own price expectation is more elastic compared to other variables in influencing supply. Finding also shows that the diference between desired and real supply is only 4.5%